Delayed Detection of Predominantly Pericentral Hydroxychloroquine Toxicity in a Dominican Patient. (July 2022) - Pandit, Saagar A.; Nair, Archana A.; Mehta, Nitish; Lee, Greg D.; Freund, K. Bailey; Modi, Yasha S.
Purpose: To describe delayed detection of pericentral hydroxychloroquine (HCQ) toxicity. Methods: 67-year-old Dominican woman with rheumatoid arthritis on HCQ presented for examination. Results: Spectral-domain optical coherence tomography (SD-OCT) demonstrated bilateral cystoid macular edema with parafoveal attenuation of the external limiting membrane (ELM) and the ellipsoid zone (EZ). ELM and EZ disruption was present in inferior macula. While subtle superior defects were present on 10-2 visual fields, superior pericentral defects were noted on 24-2 testing. Hyperautofluorescence along inferior arcades corresponded to SD-OCT and visual fields. Examination 2 years prior demonstrated nonspecific points of depression on 10-2 visual fields and normal central SD-OCT findings. EZ and ELM disruption was present in the perifoveal inferior macula. Conclusions: Early pericentral distribution of HCQ toxicity is not limited to Asian patients. Detecting pericentral HCQ toxicity involves reviewing entire macular cube on OCT. When OCT changes are suspected on parafoveal OCT B-scans, visual field testing with 24-2 may be more sensitive than 10-2.